Modeling, analysis and voltage balancing for DC distribution networks - Chew, Benjamin Si Hao (2019)
With the technological advancement in power electronics, DC LED lightings, distributed energy sources, DC energy storage systems, and the increasing use of end-user electronics, DC distribution system re-emerge as a potential system for energy savings such as in the case of DC LED lighting system for a built environment.